Summer on the island - Novak, Brenda (Mira, 2022)
After the death of her US senator father, Marlow Madsen travels to the small island off the coast of Florida where she spent summers growing up to help her mother settle the family estate. For Marlow, the trip is a chance to reconnect after too long apart. It's also the perfect escape to help her feel grounded again, one she's happy to share with friends Aida and Claire, who are hoping to hit reset on their lives, too. A leisurely beachfront summer promises the trio of women the opportunity to take deep healing breaths and explore new paths. But when her father's will reveals an earth-shattering secret that tarnishes his impeccable reputation and everything she thought she knew about her family, Marlow finds herself questioning her entire childhood, and aspects of her future. Fortunately, her friends, and the most unlikely love interest she could imagine, prove that happiness can be found no matter what, as long as the right people are by your side.